PEMELIHARAAN GELANGGANG OLAHRAGA SUDIANG UNTUK MENINGKATKAN KUALITAS INFRASTRUKTUR BANGUNAN - Dirham, Dirham; Saputra, Sulkifli Syam; Mutmainnah, Mutmainnah (Nature : National Academic Journal of Architecture, 2014)
Suding sports center built since 2004, but over the mouths there are many problems that accured in this building mainly comes to facilities and infrastructure of buildings that have been damaged. Therefor we need conduct cancening the problem by observation as well as interview techniques and the distribution of questionnaires to the respondents of the research object which in Sudiang sport center about how far the problem in infrastructure damage and GOR infrastructure.